"You plan, but you never know" – participation among people with different levels of severity of Parkinson's disease. (December 2014) - Thordardottir, Björg; Nilsson, Maria H.; Iwarsson, Susanne; Haak, Maria
Abstract Purpose: The aim of this study was to improve our understanding of important aspects of participation in everyday life for people with different levels of severity of Parkinson's disease (PD). Methods: A qualitative design was used, with empirical data obtained from focus groups. The participants had all been diagnosed with PD at least one year prior to the start of the study. Purposeful sampling was used to ensure that both sexes, with variations in age, marital status, living arrangements, education and employment, were represented. Recruitment continued until saturation was reached and resulted in 29 participants. Homogeneity within each focus group was based on self-rated PD severity (mild, moderate or severe). Findings: The aspects that influence participation at different stages of PD are that those with PD stand out in public, as a result of disease-specific features, and that the disease is unpredictable. Planning was highlighted as a strategy that is required to support participation and cope with stress and to compensate for the fact that everyday activities demanded a great deal of time and energy. Conclusion: These findings are of importance to the development of rehabilitation interventions that support people with PD in maintaining their participation in everyday life, throughout the course of the disease. Implications for Rehabilitation PD severity and disease-specific problems (e.g. freezing of gait) need to be taken into account when tackling restrictions that affect participation. Interventions that aim to facilitate participation require different components and expertise depending on PD severity, as well as on individual preferences and needs. Structuring and planning everyday life might not facilitate participation for all those with PD, but concrete measures, such as making a schedule in order to structure daily life, may benefit those with milder PD.